2020
DOI: 10.1111/medu.14352
|View full text |Cite
|
Sign up to set email alerts
|

Stereoscopic three‐dimensional visualisation technology in anatomy learning: A meta‐analysis

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 62 publications
(186 reference statements)
0
40
1
Order By: Relevance
“…However, Park et al demonstrated that a threedimensional anatomical atlas for first-year medical students could not enhance the memorization of anatomical structures [13]. Importantly, a recent meta-analysis by Bogomolova et al has shown that for learning anatomy, stereoscopic 3D is superior to monoscopic 3D [14]. The additional advantage of stereoscopic visualization compared to viewing 3D images on 2D displays, which is more prevalent in routine clinical practice, was highlighted in this report [14].…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…However, Park et al demonstrated that a threedimensional anatomical atlas for first-year medical students could not enhance the memorization of anatomical structures [13]. Importantly, a recent meta-analysis by Bogomolova et al has shown that for learning anatomy, stereoscopic 3D is superior to monoscopic 3D [14]. The additional advantage of stereoscopic visualization compared to viewing 3D images on 2D displays, which is more prevalent in routine clinical practice, was highlighted in this report [14].…”
Section: Introductionmentioning
confidence: 67%
“…Brown et al have also demonstrated that subjectively students achieved a better understanding of anatomy and pathology through stereoscopic three-dimensional images [26]. Furthermore, a recently published metaanalysis focusing on the anatomy learning supported these findings and highlighted the advantage of stereoscopic 3D over non-stereoscopic 3D [14]. However, the potential of three-dimensional volume rendering for stereoscopic visualization has not been fully exploited [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disparities in results may be due to differences in methodology, anatomical region studied, or confounding presence of additional learning resources. Results from a recent meta‐analysis by Bogomolova et al (2021) showed that a benefit of stereopsis for learning anatomy with 3D digital models was observed when participants were able to interact with and directly manipulate such models; perhaps the conflicting results of the aforementioned studies is dependent on the degree of interaction participants had with the 3D digital models. It is also possible that the nature of the stereoscopic display plays a role in its relative effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Circa 2006, a young graduate student confidently pronounced to me, ‘We already know everything about spatial ability and stereoscopic teaching methods, I'm over it’. The paper, Stereoscopic three‐dimensional visualisation technology in anatomy learning: A meta‐analysis , 1 by Bogomolova et al, highlights two things in my mind: the Dunning‐Kruger Effect 2 is alive and kicking AND we all clearly have more to learn. Reading with interest and knowledge in the area of cognitive load and development of 3D visualisation technologies (3DVT), it was refreshing to observe how the authors wove their message using solid approaches to rid us of multiple layers of bias and yield the conclusion that 3DVT has positive effects on student learning but only in interactive educational scenarios.…”
mentioning
confidence: 99%